Youth Perceptions of Sex Education at The University of Muhammadiyah Jakarta - Erlangga Putera Pamungkas; Gema Ariyanda; Muchafit Kurniawan; Sahid Hawa (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Adolescence is a period of transition from childhood to adulthood during which one undergoes psychological, cognitive, and sexual changes. Indonesian youth still lack knowledge about sexuality and reproductive health, because it is still considered taboo to convey information about it. This study aims to determine the perception of adolescents about sex education at the University of Muhammadiyah Jakarta. The factors studied were knowledge and perception. This research activity was carried out in June-July 2021. This research is qualitative research and the main informants of this research are 4 students of the Faculty of Public Health, University of Muhammadiyah Jakarta, who are not married, with 2 people each from semester 4 and semester 6. The research used a phenomenological qualitative method with data analysis based on content analysis and synthesis tables. Validation of this research data using triangulation of sources and observation of secondary data. Although the informants considered there was a controversy that sex education could protect negative things, it could also increase children's curiosity towards negative things. However, all informants considered sex education very important. Informants still view the goals of sex education as normative, according to the perception of adolescent students from the Faculty of the Public Health University of Muhammadiyah Jakarta, that the current environment directs people or teenagers to have free sex